Estágios iniciais de sucessão da vegetação do estado do Rio Grande do Sul: caracterização florística, fitossociológica e biométrica - Carvalho Junior, Luiz Alberto (2002)
This work was carried out in the vegetations in the initial stages of succession, in the different phytogeographic types of the State of Rio Grande do Sul, considering data surveyed by the Continuous Forestry Inventory of Rio Grande do Sul, aiming at classifying the initial stages vegetation (capoeira) found in the area, in dendrometric groups, utilizing multivariate statistical tecnics. Besides this, the work attempted to specify these groups in a phytosociological form (analysis for the whole State and for the different phytogeographic groups). The sample was considered satisfactory, when observed the curve sampled species x sampled area for the whole State. Three groups of succession (Capoeirinha, Average Capoeira and Capoeirão) were obtained by Cluster and discriminatory analysis, with the utilization of the dap variables, were obtained: Average height, basal area per hectare, volume per hectare, number of species per unit and number of trees per hectare, theree dendrometric groups with na accuracy of 99.1%: foreheads for discriminatory analysis. The group Capoeirinha has presented the subsequen species of bigger value of importance when observed generically, Sebastiana commersoniana, Baccharis semiserrata, Eugenia uniflora, Cupania vernalis, and Lithraea brasiliensis, as well as species which were representatives of the group or subseries, such as: Baccharis leucopappa, Bacharis articulata, Bacharis mesoneura, Bacharis pentodonta, Bacharis punctulata, Bacharis semiserrata, Bacharis spicata and Bacharis tridentata, besides the genre Eupatorium with the species: Eupatorium cruciatum, Eupatorium laevigatum, Eupatorium polystachyum, Eupatorium rufescens, Eupatorium sp..The group Capoeira Média has presented the species: Eugenia uniflora, Sebastiana commersoniana, Matayba elaegnoides, Blepharocalyx salicifolius and Daphnopsis racemosa, as species belonging to the group or subseries the species: Acacia bonariensis, Acacia tucumanensis, Achatocarpus praecox, Allophylus guaraniticus, Bauhinia microstachya, Calliandra tweediei, Campomanesia guazumifolia, Cestrum sp., Citronella paniculata, Coccoloba cordata, Eugenia uruguayensis, Miconia hyemalis, Myrceugenia glaucescens and Piper gaudichaudianum, For the group Capoeirão the species with the bigger importance value were: Allophylus edulis, Luehea divaricata, Matayba elaeagnoides, Nectandra megapotamica and Ocotea pulchella as species belonging to the group or subseries the species: Celtis pubescens, Citharexylum montevidense and Eugenia pyriformis. Considering the phytosociological analysis for the different groups, about the phytogeographic types, observing in the same way the importance values of the species, information was achieved about the types: Mixed Ombrophila Forest with the species: Ocotea puberula, Eupatorium serratum, Cupania vernalis, Lithraea brasiliensis and Luehea divaricata; Deciduous Forest with the species: Sebastiania commersoniana, Helietta apiculata, Baccharis semiserrata, Escallonia bifida and Cupania vernalis; Savannah Region with the species: Lithraea brasiliensis, Styrax leprosus, Blepharocalyx salicifolius, Eugenia uniflora and Helietta apiculata; Steppe Region with the species: Sebastiania commersoniana, Acacia caven, Schinus molle, Myrcia selloi and Scutia buxifolia; Area of Pioneer Formation with, Dodonaea viscosa, Sebastiania commersoniana, Baccharis semiserrata, Hovenia dulcis and Vitex megapotamica; Area of Ecological Tension with: Acacia bonariensis, Baccharis semiserrata, Cupania vernalis, Schinus terebinthifolius and Schinus lentiscifolius; all of them belonging to the group Capoeirinha. For the Average Capoeira group, it was obtained: Deciduous Seasonal Forest with: Eugenia uniflora, Sebastiania commersoniana, Lithraea brasiliensis e Parapiptadenia rigida; in the Savannah Region with: Sebastiania commersoniana, Dalbergia frutescens, Luehea divaricata, Eugenia uniflora and Matayba elaeagnoides.